A repressible female-specific lethal genetic system for making transgenic insect strains suitable for a sterile-release program. - Heinrich, J.C.; Scott, M.J. (Proceedings of the National Academy of Sciences of the United States of America, 2000)
We have developed a tetracycline-repressible female-specific lethal genetic system in the vinegar fly Drosophila melanogaster. One component of the system is the tetracycline-controlled transactivator gene under the control of the fat body and female-specific transcription enhancer from the yolk protein 1 gene. The other component consists of the proapoptotic gene hid under the control of a tetracycline-responsive element. Males and females of a strain carrying both components are viable on medium supplemented with tetracycline, but only males survive on normal medium. A strain with such properties would be ideal for a sterile-insect release program, which is most effective when only males are released in the field.